Added value and marketing mix of Anoa coffee products in South Konawe district after covid-19 pandemic - Muhammad Iqbal Kusumabaka Rianse; Ilma Sarimustaqiyma Rianse; Andi Awaluddin; Hadi Sudarmo (International journal of technology and education research, 2023)
One of the various leading agricultural commodities in South Konawe, and one that has undergone a good downstream process on the part of farmers, is coffee. This research aims to study and analyze the increase in added value, quality, and marketing mix of new brand Anoa coffee products after the COVID-19 pandemic. The data were collected from 18 coffee farmers in three sub-districts (Landono, Benua, and Mowila) and the home industry (CV Kopindo Sukses Bersama) and analyzed using Hayami’s method. The added value of anoa coffee products was 68%; when comparing the results before and after pandemic COVID-19, the price of raw materials for processing ground coffee after pandemic COVID-19 remained consistent. Also an increase in the added value of coffee products, such as 12%, accompanied by efforts to increase the selling price of ground coffee products. Furthermore, the marketing mix product anoa coffee has a new image packaging design (Tolaki dancers and traditional houses), so it has unique visual and cultural value on the packaging, and now they have various anoa coffee products (Robusta, Wine, anakia, and blend arabica robusta). The diversity of the product can reach all coffee connoisseurs, from the lower middle class to the upper middle class.